Liquid reflections: water imagery and the poetic self in Elizabeth Bishop’s work - Giacomassi, Priscila Célia (Texto Poético, 2026)
ln Elizabeth Bishop’s poetry, the pervasive sense of non-belonging - marked by the absence of a fixed home and the poet’s positioning between places - is expressed through distinctive strategies. Among these, water imagery stands out, particularly in poems with a dream-like atmosphere, serving as a symbolically rich vehicle for self-revelation. This study examines Bishop’s use of aquatic imagery across her work, highlighting its shifting representations, interpretive possibilities, and contribution to an oneiric ambiance. The analysis considers water’s significance within individual poems and its broader role as a medium through which aspects of the poet’s innermost self are projected and refracted. — REFLEXOS LÍQUIDOS: A IMAGÉTICA DA ÁGUA E O EU POÉTICO NA OBRA DE ELIZABETH BISHOP Na poesia de Elizabeth Bishop, o persistente sentimento de não pertencimento - marcado pela ausência de um lar fixo e pelo posicionamento do eu poético entre lugares - é expresso por meio de estratégias distintivas. Dentre elas, a imagética da água se destaca, especialmente em poemas de atmosfera onírica, funcionando como um veículo simbolicamente rico para a autorrevelação. Este estudo examina o uso de imagens aquáticas por Bishop ao longo de sua obra, destacando suas representações mutáveis, possibilidades interpretativas e contribuição para a construção de uma atmosfera onírica. A análise considera tanto a importância da água em poemas individuais quanto seu papel mais amplo como meio de projeção e reflexão do eu mais íntimo da poetisa. — Original em inglês.